Effects of rural-urban residence and education on intimate partner violence among women in Sub-Saharan Africa: a meta-analysis of health survey data - Maria Sarah Nabaggala; Tarylee Reddy; Samuel Manda (BMC, 2021)
Abstract Background Intimate Partner Violence (IPV) against women is a major public health and human rights problem worldwide. Sub-Saharan Africa (SSA) has one of the highest prevalence of IPV against women in the world. This study used meta-analysis to obtain pooled rural-urban and education attainment differences in the prevalence of IPV among ever-partnered women in SSA, and assessed whether the differences in IPV depended on the SSA region or period or women's age. Methods We analysed IPV data on 233,585 ever-partnered women aged 15-49 years from 44 demographic and health surveys conducted between 2000 and 2018 in 29 SSA countries. Random-effects meta-analyses were used to estimate overall rural-urban residence and educational differences in IPV rates among the women in SSA. Subgroup analyses were also done to investigate the sources of heterogeneity in the overall meta-analysis findings. Results The pooled prevalence of intimate partner violence was estimated to be 41.3% (37.4-45.2%). Regionally, the highest prevalence of IPV was in Middle Africa (49. 3%; 40.32-58.45), followed by East Africa (44.13%; 36.62-51.67), Southern Africa (39.36%; 34.23-44.49), and West Africa (34.30%; 27.38-41.22). The risks of experiencing IPV were significantly higher if the women had less than secondary education (RR = 1.12; 95% CI  1.07-1.22) compared to those with at least a secondary education. Generally, women who resided in a rural area had their risks of experiencing IPV increased (RR = 1.02; CI 0.96-1.06) compared to those who resided in urban areas, but the IPV increases were only significant in East Africa (RR = 1.13; CI 1.07-1.22). Conclusion In sub-Saharan Africa, intimate partner violence against women is widespread, but the levels are much higher among women with lower levels of education and residing in rural areas. Our findings have provided additional support to policies aimed at achieving SDG goals on the elimination of all forms of violence against women and girls in sub-Saharan Africa. For example, policies that advocate improved educational attainment, especially among women and communities in rural areas.